Titanium Aluminide Manufactured by Electron Beam Melting - Fager Franzén, Sanna; Karlsson, Joakim (My University, 2010)
Gamma titanium aluminides (γ-TiAl) have been recognized for decades to be suitable for aerospace applications due to their low density and high strength at elevated temperatures. However, TiAl is limited in application due to difficulties during machining which arise from the inherent brittle nature associated with intermetallic phases. Electron Beam Melting (EBM) has recently been proven as a processing method to produce complex, near net shape γ-TiAl parts with short lead times. In this report the resulting microstructure from the as-EBM built material is presented. The as-EBM-built material is treated through Hot Isostatic Pressing (HIP) and thoroughly investigated using optical microscope, SEM and FIB-SEM technologies. From the as-HIPed material different heat treatments were applied to achieve the theoretical available microstructures. The heat treated material was evaluated using SEM and grain size measurements. By using tensile testing the mechanical properties of all different treatments were evaluated. The results from investigations conclude that EBM is a feasible way to produce γ-TiAl material. Different microstructures are achievable with applicable heat treatments and process parameters from the EBM machine. By using the EBM technology γ-TiAl produced material will experience unique microstructural features with very small grain size.
Keywords: Materialvetenskap; Materialteknik; Konstruktionsmaterial; Materials Science; Materials Engineering; Construction materials